PENGARUH PENERAPAN MODEL PEMBELAJARAN GENIUS LEARNING STRATEGY TIPE OPERAN KERTAS IDE TERHADAP HASIL BELAJAR FISIKA SISWA KELAS VIII SMP N 1 DANAU KEMBAR (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2018)
This research is motivated because not yet maximal result of physics study student of class VIII SMP Negeri 1 Danau Kembar. Not maximal result of student learning caused by teaching method used by teacher have not varied and learning still centered on teacher. This study aims to determine whether the results of student physics learning by applying the learning model genius learning strategy type of paper operant paper is better than the student learning outcomes that apply the conventional learning model in class VIII SMP Negeri 1 Danau Kembar. This type of research is a quasi experimental research with Randomized Control Group Posttest Only Design research design. The sampling technique uses cluster random sampling. Genius learning strategy has eight stages namely, conducive atmosphere, connect, big picture, set goals, information entry, activation, demonstration, and review and anchor. Learning outcomes in the cognitive domain were obtained, the mean grade of the experimental class was 74.70 and the control class was 66.13. Furthermore, with t test analysis, th = 1.96 bigger than tt = 1.675 (at the real level of 0.05), thus the hypothesis is accepted. So the application of learning model genius learning strategy type operan paper idea better than the student learning outcomes that apply the conventional learning model in class VIII SMP Negeri 1 Danau Kembar.Keyword: Genius learning strategy